The concept of 'dangerousness' in the people's Republic of China and its impace on the treatment of prisoners - Epstein, Edward Jay (The British journal of criminology, 1996)
Throughout the history of the People's Republic of China criminal process and administrative sanctions have been viewed as a medium for the exercise of coercive state power against those who would undermine the existing political order, and Chinese socialist political ideology has consistently justified this position. Dangerousness is a concept informed by those political considerations necessary to maintain order in a one-party socialist state. Dangerousness forms an element of both criminality and sentencing in China. Dangerousness to society is an explicit component of liability under the Criminal Law and liability for administrative punishment. It is also a major factor in determining sentences. The Chinese system's preoccupation with dangerousness to society is also demonstrated by the use of regular anti-crime campaigns which target activities viewed as being particularly dangerous to society at a given time. While the concept of individual dangerousness is not codified, Chinese scholars have in recent years argued that it is an implicit element in determining the appropriate sentence for individual offenders. In fact, individual dangerousness is also an important factor in deciding whether or not to commit a person to Re-education Through Labour or Forced Job Placement, which are administrative sanctions. The concept of dangerousness also plays a role in the differentiation between various categories of incarcerated persons and their treatment. Prisons and remote labour camps are thus reserved for counterrevolutionaries, prisoners serving at least ten-year sentences or with knowledge of state secrets, recidivists, those who resist reform and the like. Treatment of individual prisoners and detainees also depends on perceived levels of the dangerousness they pose to society and each other, whether in the reform technique employed during incarceration or in deciding on early release and Forced Job Placement